TINGKAT PEMANFAATAN, PERILAKU PEMELIHARAAN DAN KONDISI FASILITAS SANITASI MANDI, CUCI DAN KAKUS (MCK) PLUS++ DI KELURAHAN SEMULA JADI DAN KELURAHAN BETING KUALA KAPIAS KOTA TANJUNG BALAI TAHUN 2013 - ade maulida gultom (Lingkungan dan Kesehatan Kerja, 2014)
Utilization rate, maintenance behavior and conditions of sanitation facilities of bath, wash and toilet rooms (MCK) Plus++ at Semula Jadi and Beting Kuala Kapias village in the district of Tanjungbalai in 2013. MCK Plus++ as same as communal bathrooms in general. It called "Plus++" because the human manure can be processed into biogas at the location (biodigester) and liquid waste deposited in settler-settler before discharge into water bodies (environmentally friendly).  The purpose of this research is to understand a description about the utilization rate, maintenance behaviors and conditions of MCK Plus++ at the district of Semula Jadi and Beting Kuala Kapias village in the district of Tanjungbalai.  The type of research was descriptive survey, with an overview of utilization and maintenance behavior (knowledge and attitude) and condition of MCK Plus++ at both of the villages, with a population of 20 people in the Semula Jadi Village and 36 people in the Beting Kuala Kapias Village. The results showed that the respondents knowledge and attitudes at the Semula Jadi Village was good in fact produces utilization and maintenance rate of MCK Plus++ was moderate. At Beting Kuala Kapias Village, a good knowledge and a moderate attitudes can produces utilization and maintenance rate of MCK Plus++ was good.  In addition, the results showed that the condition / quality of MCK Plus++ at both of the villages was classified into good category. Based on these results expected for the Public Works Department to continue improving the quality / condition of MCK Plus++ especially for Semula Jadi Village. For the Department of Health and YAKMI expected to continue support improving the utilization and maintenance of MCK Plus++ at both of the villages. For the user community of MCK Plus++ is expected would like to provide gas supplier distribution pipe. Keywords: Utilization rate, Maintenance Behavior, MCK Plus++